Capital Analysis, Human Resource Professionalism and Technology on Income of Small Medium Industry (SMI) Crafts in Padang City - Siti Rahmi; Popi Fauziati; Sinya Dirmayanti; Nailal Husna (Jurnal Manajemen Universitas Bung Hatta, 2023)
This study intends to examine the impact of capital, human resource professionalism, and technology on IKM Crafts' revenue in the city of Padang. This study makes use of quantitative research, namely by examining the financial resources, human capital, owners of the IKM, and technology employed by the IKM. MSMEs, or micro, small, and medium-sized businesses, are crucial for boosting regional and national economic resilience. And serves as the foundation of the public economic system. aimed at minimizing the issue of income inequality and the disparity between corporate actors, or at reducing poverty and increasing employment. The growth of MSMEs has the potential to broaden the economy and contribute significantly to quickening structural change. A sample of IKM Crafts from the city of Padang was used in this investigation. Multiple linear regression has been employed as the data analysis method in this study. The simultaneous test (F-test) and partial test (t-test) were used in this study to test the hypothesis and identify the relationship between the variables. The normality test, heteroscedasticity test, and multicollinearity test are the traditional assumption tests applied in this study. The results of this study indicate that the variables of capital and human resources have a significant positive effect on income. technology variable has no significant effect on income.